On Dreams and Motivation: Comparison of Freud’s and Hobson’s Views - Boag, Simon (Frontiers in Psychology, 2017)
The merits of Freudian dream theory continue to be debated and both supporters and critics appeal to empirical evidence to support their respective positions. What receives much less attention is the theoretical coherency of either Freudian dream theory or alternative perspectives. This paper examines Freudian dream theory and J. Allan Hobson’s alternative position by addressing the role of motivation in dreams. This paper first discusses motivation in Freudian theory and its relation to dreams and disguise-censorship. The role of motivation in Hobson’s theory is then considered. Hobson’s claim that dream plot and content selection is random and based on design error and functional imbalance is then discussed in relation to the protoconsciousness theory proposal that dreams serve an adaptive function. While there are apparent inconsistencies in Hobson’s position, his appeal to emotions and instincts provides a preliminary platform for understanding the role of motivation in dreams that is consonant with the Freudian position.